Inhibition of Mild Steel Corrosion in Acidic Medium by Aqueous Extract of Tridax procumbens L. - G. Ilayaraja; A. R. Sasieekhumar; P. Dhanakodi (E-Journal of Chemistry)
The inhibition efficiency (IE) of an aqueous extract of Tridax procumbens L. in controlling corrosion of mild steel has been investigated by weight loss method in the absence and presence of corrosion inhibitor at different time interval at room temperature. The result showed that the corrosion inhibition efficiency of these compounds was found to vary with different time interval and different acid concentration. Also, it was found that the corrosion inhibition behavior of Tridax procumbens L. is greater in sulphuric acid than hydrochloric acid medium. So Tridax procumbens L. can be used as a good inhibitor for preventing mild steel material.